The World of Animals - Joanna Harrelson; Deborah J. Glauer (EDIS)
Produced by the Florida 4-H Youth Developmemt Program, University of Florida Cooperative Extension, Institute of Food and Agricultural Sciences, June, 1996; reviewed June 2002.